2010
DOI: 10.1093/hmg/ddq007
|View full text |Cite
|
Sign up to set email alerts
|

Arginines of the RGG box regulate FMRP association with polyribosomes and mRNA

Abstract: Fragile X syndrome is caused by the loss of expression of the fragile X mental retardation protein, FMRP. FMRP is an RNA-binding protein that is highly expressed in neurons and undergoes multiple post-translational modifications including methylation on arginine. FMRP is methylated on the high-affinity RNA-binding motif, the RGG box, at positions 533, 538, 543 and 545 of murine FMRP. To identify the arginines important for FMRP function, we examined their role in polyribosome and mRNA association. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 52 publications
5
98
0
3
Order By: Relevance
“…51). It is intriguing that Arg10 and Arg15, involved in polyribosome binding (14), are among four arginines targeted for methylation in FMRP and their methylation decreases RNA binding affinity (14,52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…51). It is intriguing that Arg10 and Arg15, involved in polyribosome binding (14), are among four arginines targeted for methylation in FMRP and their methylation decreases RNA binding affinity (14,52).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, binding of FMRP to G-rich RNAs in vitro requires only the RGG motif, which specifically interacts with natural and in vitro selected G-quadruplex-containing RNAs such as a 35-nucleotide sc1 RNA (21,(26)(27)(28)(29). Recent studies showed that G-quadruplexes facilitate mRNA interactions with ribosome-bound FMRP (30), whereas the RGG motif, in addition to mRNA binding, contributes to association with ribosomes and proteins and translational control (14,(31)(32)(33)(34). The RGG motif is well conserved in FMRP of vertebrates but differs significantly from…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The RGG box of FMRP was shown to be responsible for the interaction with the G-quadruplex secondary structure in the MAP1B 5Ј-UTR (43). Therefore, methylation of RGG motifs in FMRP by PMRT1 might regulate the interaction of FMRP with polyribosomes and G-quadruplex-containing mRNAs (81). In addition, members of the hnRNP A family were reported to destabilize G-quadruplex structures by a so-far unknown mechanism (44,82).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins that contain simple unstructured repeats have been found to act as RNA chaperones 5,6 and the intrinsically unstructured regions of several RNA chaperones have been proposed to possess such chaperone activity. 4,5 RS domains consist of several (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) copies of the RS dipeptide, irregularly interrupted by other amino acids. RS domains can directly bind RNA and themselves 7,8 in a rather non-specific manner.…”
Section: F or Many Experimental Biologists Inmentioning
confidence: 99%